Joint Communication to the European Parliament, The Council, The European Economic and Social Committee and the Committee of the Regions
The European Union (EU) is in the Arctic. As a geopolitical power, the EU has strategic and day-to-day interests, both in the European Arctic and the broader Arctic region. The EU also has a fundamental interest in supporting multilateral cooperation in the Arctic and in working to ensure that it remains safe, stable, sustainable, peaceful and prosperous. Being a major economic player, it shares the responsibility for global sustainable development, including in the Arctic regions, and for the livelihood of inhabitants, including Indigenous Peoples. The EU exerts a significant impact on the Arctic through its environmental footprint and demand for resources and products originating there.